Kepemimpinan Situasional di Lembaga Pendidikan Swasta - Bakri, Nofri; Yusuf, Dodi Muhmmad; Asmendri, Asmendri; Sari, Milya (Jurnal Ilmiah Wahana Pendidikan, 2024)
Educational leadership is a way that is inherent in a leader in carrying out his duties through the people he leads in educational institutions. Educational institutions in Indonesia consist of state educational institutions and private educational institutions. Leadership in private educational institutions, both schools and universities, is essentially obtained through stages that have been determined by government regulations and adapted to the policies or regulations of private institutions without reducing what has been stipulated in government regulations to serve as guidelines. This research aims to provide an overview of educational leadership in private educational institutions regarding how to obtain it and their responsibilities in leading. The research method used is a library research by exploring information through literature regarding situational leadership in private educational institutions. Situational leadership style is an approach to leadership that encourages leaders to understand their behavior, the behavior of subordinates, and the situation before using a particular leadership style.